Quantification of indirect waste generation and treatment arising from Australian household consumption: A waste input-output analysis. (10th June 2020) - He, He; Reynolds, Christian John; Hadjikakou, Michalis; Holyoak, Nicholas; Boland, John
Abstract: Waste input-output (WIO) model is a suitable method to explore the nexus between economic activities and waste management. Contemporary research that typically explores this nexus follows two main aspects: either they consider Final demand as a whole, or they identify the nexus between households, with different types of socio-demographic indicators and household waste generation. However, it is complex to apply the WIO model from the perspective of household consumption— a major component of Final demand — because of a lack of economic and environmental data related to household consumption. This paper proposes a new perspective, applying the WIO model to assess the nexus between different patterns of household consumption and indirect waste generation and treatment. This novelty is to combine macro- and micro-economic and environmental data related to Australian industrial sectors, different patterns of household consumption (Mosaic data), and direct waste generation into the WIO model for exploring this nexus in two scenarios. Results indicate that the total amount of indirect waste generation caused by B05 (couples without children who spend the majority of their time at the office) are 99.24 kg more than that of D16 (couples without children who are retired and stay at home) for scenario I. The correlation coefficients for differences of output of economy and indirect waste generation between B05 and D16 are 0.9796 and 0.9773 in scenarios I and II, respectively. Sensitivity analysis indicates the change of the amount of direct waste generation in a reasonable range cannot dramatically affect the major economic activities and waste generation. This research suggests a different perspective of household consumption to estimate indirect waste generation through a WIO model to provide more reliable information for waste management in the supply chain. Graphical abstract: Image 1 Highlights: We examine supply chain indirect waste generation caused by household consumption. Multiple scenarios and types of households investigated in Australian case study. Majority of waste caused by Household consumption in supply chain, not in household. Working couples (B05) generate more indirect waste than retired couples (D16). Methods for decreasing indirect waste in the supply chain proposed.